The Influence of Teacher Professionalism and School Culture on Education Quality at Private Vocational High Schools in Indramayu - Satria Nugraha, Rizki; Dekawati, Ipong (Universitas Ahmad Dahlan, 2023)
Education is essential in enhancing life quality. It fosters societal benefits and prosperity. The necessity of education extends its significance to individuals, societies, and even nations. Multiple elements contribute to enhancing education quality, encompassing teacher professionalism and school culture. Hence, this study assesses the impact of teacher professionalism and school culture on education quality, individually and collectively. The research utilizes a descriptive and verificative methodology, employing Likert scale questionnaires to gather data from 59 teachers. Regression analysis techniques process the data, and significance is assessed via F-tests. The findings indicate: (1) Teacher professionalism significantly and positively affects education quality; (2) School culture similarly exerts a positive and significant influence; (3) Simultaneously, teacher professionalism and school culture significantly enhance education quality. In light of these outcomes, the author proposes (1) Enhancing teacher professionalism through self-growth, academic participation, and adherence to ethical standards, further enriched by engaging in educational activities and community collaborations facilitated by school committees. (2) For improved education quality, emphasize the underrepresented dimension of norms within school culture, integrate various educational norms into school life and social interactions, and foster alignment with internal school policies and government regulations